The astronaut wives club : a true story - Koppel, Lily. (New York : Grand Central Publishing, 2013)
"As America's Mercury Seven astronauts were launched on missions, television cameras focused on the brave smiles of their young wives. Together with the other wives they formed the Astronaut Wives Club, meeting regularly to provide support and friendship. This tells the real story of the women who stood beside some of the biggest heroes in American history"--
Keywords: Astronauts' spouses -- Texas -- Houston -- Biography; Women -- Texas -- Houston -- Social life and customs -- 20th century; Astronautics -- United States -- History